2013
DOI: 10.13168/agg.2013.0037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recent GOCE geopotential models over the area of Poland

Abstract: The dedicated satellite gravity missions have provided homogeneous and uniformly accurate information on the long and medium wavelengths of the Earth's gravity field. Since the launch of GOCE satellite gravimetry mission by the European Space Agency (ESA) in 2009, several global geopotential models (GGMs) have been published. This study evaluates the recent GOCE-based GGMs over the area of Poland. The evaluation has been performed with the use of the EGM08 as well as high-precision GPS/levelling control traver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Further analysis concerning the accuracy evaluation of one GOCE-only GGM, four GOCE/GRACE satellite-only GGMs, and one GOCE/GRACE GGM combined with terrestrial gravity data showed an extremely good agreement of those models with the EGM08 (Table 1). It also demonstrated the potentiality of using the high-precision and high-resolution GPS/levelling control traverse for the evaluation of GGMs (Godah and Krynski, 2013a). New developments in processing GOCE data resulted in new releases of GOCEbased GGMs.…”
Section: Evaluation Of Goce-based Ggmsmentioning
confidence: 96%
“…Further analysis concerning the accuracy evaluation of one GOCE-only GGM, four GOCE/GRACE satellite-only GGMs, and one GOCE/GRACE GGM combined with terrestrial gravity data showed an extremely good agreement of those models with the EGM08 (Table 1). It also demonstrated the potentiality of using the high-precision and high-resolution GPS/levelling control traverse for the evaluation of GGMs (Godah and Krynski, 2013a). New developments in processing GOCE data resulted in new releases of GOCEbased GGMs.…”
Section: Evaluation Of Goce-based Ggmsmentioning
confidence: 96%
“…Adaptation of the International Height Reference Frame (Mäkinen, 2021), introduced the mean tide as a base of the Global Geopotential Models (GGM) (Ince et al, 2019). By using the same tidal concept, fitting the GGMs into levelling networks should be more accurate, and it should produce a better-tailored geoid/ quasi-geoid to height datum (Godah, 2013;Kaloop et al, 2022). This situation provides another opportunity to use GNSS observations in ordinary surveying work, that until recently had been reserved only for spirit levelling or total station.…”
Section: Levelling Networkmentioning
confidence: 99%